Kolokwializmy we współczesnej prasie: funkcje i uwarunkowania (na materiale „Gazety Wyborczej” i „Nowej Gazety”) - Kiklewicz, Aleksander (Przegląd Wschodnioeuropejski, 2025)
The author examines the state of colloquialization of the language of contemporary journalistic expression, comparing texts published in the liberal Polish “Gazeta Wyborcza” and the Russian “Novaya Gazeta”. The phenomenon of colloquialization in journalistic texts is considered in the context of the democratization of the societies of Central and Eastern Europe at the turn of the 1980s and 1990s. Other conditions are also taken into account: postmodern tendencies in various areas of culture, as well as traditions common to Slavic cultures. Parametric analysis of profanity concerns the mode of its use (narrative or quotation), semantic modifications and phrasing.